Narcissistic susceptibility to conspiracy beliefs exaggerated by education, reduced by cognitive reflection - Cosgrove, Tylor J.; Murphy, Christopher P. (Frontiers in Psychology, 2023)
Conspiracy theories are alternate viewpoints of provided explanations; sensational stories revolving around small groups exerting control for nefarious reasons. Recent events and research have outlined myriad negative social and personal outcomes for those who endorse them. Prior research suggests several predictors of susceptibility to conspiracy theories, including narcissistic personality traits (grandiosity, need for uniqueness), cognitive processes (critical thinking, confirmation bias) and lack of education. Study one utilised an international survey (N = 323) to investigate the role of education as a protective tool in the relationship between narcissistic traits and conspiratorial beliefs. Support was found for the hypotheses that higher levels of narcissistic traits would predict conspiracy theory endorsement. Higher education and STEM education were associated with lower levels of conspiracy endorsement, however all significant moderations indicated that for narcissistic individuals, education conversely increased their likelihood of adopting conspiracy beliefs, contrary to expectation. To investigate this further, study two analysed a large-scale publicly available dataset (N = 51,404) to assess the relationship between narcissism, critical thinking and conspiracy beliefs pertaining to the COVID-19 pandemic. As expected, analysis found narcissism and poor critical thinking as predictors of conspiracy beliefs. Stronger critical thinking skills were found to be protective, moderating and reducing the impact of narcissism on endorsement of conspiracy theories. The relationship between collective narcissism and conspiracy belief was also moderated by critical thinking, however the effect was more moderate. Findings are discussed in terms of educations impact for narcissistic individuals and the differences between cognitively and socially motivated conspiratorial beliefs. The findings improve understanding of both the role and limitations of education/critical thinking skills as protective factors against conspiracy theory endorsement.